2006
DOI: 10.1007/s00192-006-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated postvoid residual in women with pelvic floor disorders: prevalence and associated risk factors

Abstract: A retrospective case-control study was designed to assess risks for elevated post void residual (PVR) in women with pelvic floor disorders. The 1,399 women underwent evaluation including standardized questionnaire, examination, and catheterized PVR. Elevated PVR was defined as > or =100 ml and anterior and apical prolapse was defined as at or beyond the hymen. Overall, the prevalence of elevated PVR was 11%. After matching, the absence of stress incontinence symptoms (OR 0.55, CI 0.33-0.92), the symptoms of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
3
24
0
2
Order By: Relevance
“…Our results confirmed previous data which demonstrated that advanced prolapse and aging are independent predictors for urinary retention [5,7,9]. In a previous study done by Groutz et al, the prevalence of voiding dysfunction was higher among elderly patients [7].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results confirmed previous data which demonstrated that advanced prolapse and aging are independent predictors for urinary retention [5,7,9]. In a previous study done by Groutz et al, the prevalence of voiding dysfunction was higher among elderly patients [7].…”
Section: Discussionsupporting
confidence: 82%
“…Although obstructive voiding symptoms were commonly reported in this population, these symptoms did not reflect the actual rates of urinary retention. Our data is consistent with previous investigators who also found a poor correlation between obstructive voiding symptoms and urinary retention in women [8,9]. Before this study, we hypothesized that women with higher PVR will have more prominent obstructive symptoms; therefore, we arbitrarily chose the volume of 150 ml rather than 100 ml as the cutoff for urinary retention.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…PVR measurement methodology has considerable variation [3][4][5][6] matched by similar variation in the results of scientific studies on this parameter [3][4][5][6][7]. In many other PVR studies, the exact methodology is either unclear or not validated or both.…”
Section: Introductionmentioning
confidence: 99%